(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
It is known that the maintenance of a machine consists of a large number of operations, which, by their nature and conditions of execution, can be combined into certain groups, covering the cycle of maintenance work. The main task of the point of final washing of machines is the high quality of work performed with the least amount of water and the highest labor productivity. The article considers an approach to the economical use of water at the point of final washing of the fleet of automotive vehicles in military units. The use of a washing machine brand KARCHER K7 1.168-502.0 in the maintenance of automotive equipment during the final washing of cars is justified.